FORMULASI DAKWAH PADA ERA NEW NORMAL DI WILAYAH TENGAH, ACEH - Nurliana Nurliana (An Nadwah, 2021)
This study aims to determine the methods and materials in delivering da'wahused by da'i in Central Aceh Regency during the corona period. The pandemicperiod has been running for approximately two years, which has changed alllines of life from normal life. This makes the da'i must have the skills andabilities in choosing the media and materials to be delivered to their mad'u.Da'wah still has to be carried out but with a different method compared tonormal times. The key informants in this research are preachers who are in theCentral Aceh region. The research method used is a descriptive qualitativemethod and the findings of this study are that the material presented by apreacher must cover the fields of economics, psychology, and encourage thepublic to always comply with government recommendations to always maintainhealth protocols to prevent the spread of the corona virus.